O conselho nacional do trabalho pós-reforma de 1934: uma análise sobre a atuação do conselho nos julgamentos dos conflitos trabalhistas envolvendo o movimento grevista - Souza, Yulliana Demitrieva Ananda Pinto (Universidade Federal Rural do Semi-Árido, 2021)
The objective of this research is to study the performance of the National Labor Council - CNT- after the institutional reform that took place through Decree No. 24,784, of July 14, 1934, as well as the treatment given by the council to the cases of workers who were involved in wallist movements of the time. The study will focus specifically on the period from 1934 to 1937 and will deal with cases that came to the council and dealt with conflicts involving the workers' right to strike that marked this period. This gap in time was chosen with a view to being marked by great instability in institutions and diversity of political events. For the development of the research, historical-legal methods and literature review will be used, in addition to the conception of the history of institutions, in order to better understand the historical context in which the CNT was inserted, in addition to analyzing how it behaved in face of the demands that reached its purview. For this, it will refer to administrative proceedings that were being processed within the scope of the CNT. In addition, analyzes carried out by other authors will also be used. Given the importance of this institution, the present work will study the CNT from the year 1934 onwards, as it is from that period onwards that the body begins to play its role as a judging body in a significant way. Thus, we will try to reconstruct the history of the institution, as well as understand how the CNT applied the law and positioned itself in its decisions when it came to cases involving political-labor issues, more precisely about the strike movements of the time.
Keywords: Conselho Nacional do Trabalho; Direito de greve; Reforma; História Institucional; National Labor Council; Right to strike; Remodeling; Institutional History; CIENCIAS SOCIAIS APLICADAS::DIREITO